Formal support – expectations of parents of children with disabilities - Šarčević Ivić-Hofman, Katarina; Wagner Jakab, Ana (Specijalna edukacija i rehabilitacija, 2023)
Introduction: Parents of children with developmental disabilities receive many different forms of support, including formal support provided by professionals from different systems. Aim: The aim of this study was to examine the differences in expectations of the type of formal support by parents of children with developmental disabilities with regard to their sociodemographic characteristics. Methodology: In total, 152 parents participated in the study, out of which 63.8% were female and 36.2% were male. The participants’ average age was 38 years. Data was collected using a questionnaire specifically designed for the purpose of this study, which is a component of a large-scale research study on early support provided to children with developmental disabilities and their parents. The first part of the questionnaire concerns sociodemographic characteristics, while the second part deals with the parents’ expectations of the type of formal support. Results: The results of this study show that there is a statistically significant difference in the expectations of the type of formal support by the parents of children with developmental disabilities with regard to two sociodemographic characteristics, namely the self-evaluated financial wellbeing and the level of education. Conclusion: This study shows that parents with higher levels of education and better financial wellbeing have different expectations of the type of formal support than parents with lower levels of education and lower income. These differences should be, therefore, taken into account during the processes of planning and providing support.
Keywords: parents; children with developmental disabilities; formal support